Effect of Family Support Intervention towards Quality of Life with Elderly’s Hypertension in Community - Raden Siti Maryam; Yeti Resnayati; Ni Made Riasmini; Citra Windani Mambang Sari (Jurnal Keperawatan Padjadjaran, 2018)
The quality of life of the elderly is influenced by physical, psychological, social and environmental factors. These four factors desperately need family support as a support system for the elderly. This study aims to determine the effect of family support intervention on the quality of life of elderly hypertension in Community Area Cipayung Puskesmas East Jakarta. The research method used quasi-experiment with control group design. The sampling strategy used multistage random sampling with 30 samples for the intervention group and 30 for the control group. This study were implemented during four weeks. Statistical test using dependent t-test and independent t-test. There was a significant difference in the mean elderly quality of life with hypertension after the intervention of family support program in the intervention group compared with the control group (M= 93.67 ± 6.08, p-value 0.012). In conclusion, this study showed that there were differences in mean older people quality of life with hypertension in the intervention group compared with the control group after the intervention of family support program. The resulting family support interventions can serve as the foundation for policy and health service providers in order to implement various interventions related to family empowerment to improve the quality of life older people with hypertension in the community.